Perceptions of community-based field workers on the effect of a longitudinal biomedical research project on their sustainable livelihoods - Christabelle S. Moyo; Joseph Francis; Pascal O. Bessong (BMC, 2017)
Abstract Background Researchers involved in biomedical community-based projects rarely seek the perspectives of community fieldworkers, who are the 'foot soldiers' in such projects. Understanding the effect of biomedical research on community-based field workers could identify benefits and shortfalls that may be crucial to the success of community-based studies. The present study explored the perceptions of community-based field workers on the effect of the Etiology, Risk Factors and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development Project" (MAL-ED) South Africa on their tangible and intangible capital which together comprise sustainable livelihoods. Methods The study was conducted in Dzimauli community in Limpopo Province of South Africa between January-February 2016. The sustainable livelihoods framework was used to query community-based field workers' perspectives of both tangible assets such as income and physical assets and intangible assets such as social capital, confidence, and skills. Data were collected through twenty one individual in-depth interviews and one focus group discussion. Data were analysed using the Thematic Content Analysis approach supported by ATLAS.ti, version 7.5.10 software. Results All the field workers indicated that they benefitted from the MAL-ED South Africa project. The benefits included intangible assets such as acquisition of knowledge and skills, stronger social capital and personal development. Additionally, all indicated that MAL-ED South Africa provided them with the tangible assets of increased income and physical assets. Observations obtained from the focus group discussion and the community-based leaders concurred with the findings from the in-depth interviews. Additionally, some field workers expressed the desire for training in public relations, communication, problem solving and confidence building. Conclusions The MAL-ED South Africa, biomedical research project, had positive effects on tangible and intangible assets that compose the sustainable livelihoods of community-based fieldworkers. However, the field workers expressed the need to acquire social skills to enable them carry out their duties more efficiently.